Shoulderpads and shagpile: architectural referencing in the television series Gloss - Tyler, Linda (Architectural History Aotearoa, 2009)
Before Television New Zealand closed its drama department in 1988 and production became outsourced, 55 episodes of the memorable series Gloss had been made at in the Browns Bay sound studio in Auckland. Screening between 1987 and 1990, the series was based on the experiences of writer Rosemary McLeod's years in the internecine world of women's magazines. Revolving around the machinations of fictional magazine editor and high priestess of fashion Maxine Redfern and her dynastic family, the series deployed architectural detail as readily as it did Liz Mitchell's costume designs in order to evoke an era of conspicuous consumption. Sumptuous production designs characterised the sets, with the interiors of the offices of the fictional magazine Gloss itself remarkable for their evocation of glamour and glitz. Domestic spaces inhabited by the extraordinary characters also conveyed materialism and superficiality through furnishings and design, doing much to contribute to characterisation of Aucklanders as immoral show-offs with poor value systems. The trappings of success in a materialistic world included the worst features of postmodern architecture, it would seem. As the title song for the series went, “It's the gilt off the gingerbread/The icing on the cake/It's monuments and mirrorglass/The city's on the make/Devil take the hindmost/So no one counts the cost/Such a sweet seduction/Glosssssssss."